Partnering in engineering projects: Four dimensions of supply chain integration. Issue 1 (March 2015) - Eriksson, Per Erik
Abstract Although the interest of partnering and supply chain integration (SCI) has increased in various industries, there is still a lack of comprehensive conceptual and practical frameworks that enable both a detailed and systemic understanding of integration in project-based supply chains. In this paper a theoretical framework is developed, based on general SCI literature, but adapted to a project-based context. Integration in project-based supply chains is a multi-dimensional construct, including the four dimensions strength, scope, duration, and depth of integration. Empirical findings from a multiple case study of four engineering projects indicate that these four dimensions are critical when conceptualizing and implementing partnering in engineering projects. The results show that there are strong interdependencies among the four dimensions, suggesting that it is crucial to manage them simultaneously and systemically rather than in isolation. Consequently, it is not enough to decide on the extent to which suitable integrative activities and technologies should be implemented to strengthen integration in project-based supply chains. The integrative activities and technologies must also be implemented together with the right companies (scope), at the right time (duration), and with the right people in the companies (depth).